Microbiocenosis of Anthropogenically Transformed Soils: Microbiota of urban soils - Lyudmila I. Zayinitdinova; Rokhila N. Juraeva; ikolay A. Lazutin; Aziza M. Mavjudova; Bekmukhamedova, Nigora K.; Ergashev, Rustambek B. (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
A microbiological examination of the soils, polluted with different types of urban wastewater (Tashkent city), aiming determination of the microbial diversity and characterization of the bacterial community was carried out. The examination was conducted with use of classical microbiological methods with cultivation of samples on elective nutrient media. The soil sampling was carried out during winter season and period of plants’ vegetation. As result of examination the qualitative and quantitative characteristics of the bacterial community were determined and the microbial diversity was established. The predominant microorganisms of this community, capable to active functioning at chloride concentrations of the environment for up to 10 % and possessing high remediation potential towards biological and chemical pollutants, have been isolated. Rare strains belonging to the genus Amycolatopsis, which, in contrast to typical representatives of this genus, have the ability to form a water-soluble blue pigment, have been isolated. It was established that typical representatives of microbial biota, such as heterotrophic microorganisms Bacillus, Pseudomonas and actinomycetes, possess significant remediation potential towards biological and chemical pollution. It was determined that pollution of the soil caused by anthropogenic factors at the end of the day leads to decrease in species diversity and changes in composition of the soil microbiocenosis. The results obtained convincingly testify perspectives of biomonitoring and possible use of microorganisms in the processes of soil rehabilitation. The introduction of pollutant-resistant microorganisms, which are capable to degrade them, may become a practical approach for soil cleansing in the future.